2018
DOI: 10.1515/amsil-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

On a Functional Equation Related to Two-Sided Centralizers

Abstract: Abstract. The main aim of this manuscript is to prove the following result. Let n > 2 be a fixed integer and R be a k-torsion free semiprime ring with identity, where k ∈ {2, n − 1, n}. Let us assume that for the additive mappingis also fulfilled. Then T is a two-sided centralizer.In this paper R will denote an associative ring with center Z(R). For an integer n > 1, a ring R is said to be n-torsion free, if for x ∈ R, nx = 0 implies x = 0. The expression xy − yx will be marked by [x, y]. The ring R is prime i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Vukman [22] showed that an additive mapping T : R → R, where R is a 2-torsion free semiprime ring, satisfying 2T (x 2 ) = T (x)x + xT (x) for all x ∈ R, is a centralizer. To read more about centralizers, we refer the readers to some recent papers [2,3,6,7,13,14,15,19,20,21,23], where further references can be found. So far, many mathematicians have investigated Jordan centralizers on triangular rings (or algebras) with unity, see, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Vukman [22] showed that an additive mapping T : R → R, where R is a 2-torsion free semiprime ring, satisfying 2T (x 2 ) = T (x)x + xT (x) for all x ∈ R, is a centralizer. To read more about centralizers, we refer the readers to some recent papers [2,3,6,7,13,14,15,19,20,21,23], where further references can be found. So far, many mathematicians have investigated Jordan centralizers on triangular rings (or algebras) with unity, see, e.g.…”
Section: Introductionmentioning
confidence: 99%